Artificial Intelligence Readiness, Digital Transformation Capability, Organizational Agility, Innovation Ambidexterity, and Sustainable Competitive Advantage: A Structural Equation Modeling Approach - Torres, Gabriela; Brown, Nathaniel; Nowak, Katarzyna (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2026)
Objective: This study aimed to examine the structural relationships among artificial intelligence readiness, digital transformation capability, organizational agility, innovation ambidexterity, and sustainable competitive advantage and to evaluate the direct and indirect pathways through which these organizational capabilities contribute to long-term competitive success.Methods and Materials: This quantitative study employed a cross-sectional survey design and Structural Equation Modeling (SEM) to test the proposed conceptual framework. The study population consisted of managers, executives, digital transformation specialists, and innovation professionals employed in medium-sized and large organizations across Canada. Using a stratified random sampling approach, data were collected from 587 participants through a structured questionnaire measuring artificial intelligence readiness, digital transformation capability, organizational agility, innovation ambidexterity, and sustainable competitive advantage. The psychometric properties of the measurement model were assessed using Confirmatory Factor Analysis (CFA), composite reliability, and convergent and discriminant validity tests. Structural relationships were examined using maximum likelihood estimation in AMOS 26, while model adequacy was evaluated through multiple goodness-of-fit indices.Findings: The measurement model demonstrated excellent fit to the data (χ²/df = 2.41, CFI = 0.957, TLI = 0.951, IFI = 0.958, GFI = 0.921, AGFI = 0.903, RMSEA = 0.049, SRMR = 0.042). Artificial intelligence readiness exerted significant positive effects on digital transformation capability (β = 0.68, p < .001) and organizational agility (β = 0.24, p < .001). Digital transformation capability positively influenced organizational agility (β = 0.53, p < .001) and innovation ambidexterity (β = 0.41, p < .001). Organizational agility significantly enhanced innovation ambidexterity (β = 0.47, p < .001) and sustainable competitive advantage (β = 0.34, p < .001). Innovation ambidexterity emerged as the strongest direct predictor of sustainable competitive advantage (β = 0.49, p < .001). The model explained 46% of the variance in organizational agility, 61% of the variance in innovation ambidexterity, and 69% of the variance in sustainable competitive advantage.Conclusion: The findings indicate that artificial intelligence readiness serves as a foundational capability that strengthens digital transformation and organizational agility, which subsequently foster innovation ambidexterity and sustainable competitive advantage. The study highlights the strategic importance of integrating technological readiness, digital transformation initiatives, agile organizational structures, and balanced innovation practices to achieve enduring competitive performance in dynamic and technology-intensive business environments.